FAM19A4/miR124-2 methylation analysis as a triage test for HPV-positive women: cross-sectional and longitudinal data from a Dutch screening cohort. (January 2021) - Vink, F.J.; Lissenberg-Witte, B.I.; Meijer, C.J.L.M.; Berkhof, J.; van Kemenade, F.J.; Siebers, A.G.; Steenbergen, R.D.M.; Bleeker, M.C.G.; Heideman, D.A.M.
Abstract: Objectives: The aim was to evaluate the cross-sectional and long-term triage performance of FAM19A4/miR124-2 methylation analysis in human papillomavirus (HPV)-based cervical screening. Methods: We conducted a post hoc analysis within a Dutch population-based HPV-positive study cohort of women aged 30–60 years ( n = 979). Cross-sectional cervical intraepithelial neoplasia (CIN) 3+ sensitivity, specificity, positive predictive value and negative predictive value as well as cumulative CIN3+ or cervical cancer risks after 9 and 14 years were compared for three baseline triage strategies: (1) cytology, (2) FAM19A4/miR124-2 methylation analysis and (3) combined FAM19A4/miR124-2 methylation with cytology. Results: CIN3+ sensitivity of FAM19A4/miR124-2 methylation analysis was similar to that of cytology (71.3% vs 76.0%, ratio 0.94, 95% CI 0.84 to 1.05), at a lower specificity (78.3% vs 87.0%, ratio 0.90, 95% CI 0.86 to 0.94). Combining FAM19A4/miR124-2 methylation analysis with cytology resulted in a CIN3+ sensitivity of 84.6% (95% CI 78.3 to 90.8) at a specificity of 69.6% (95% CI 66.5 to 72.7). Similar 9- and 14-year CIN3+ risks for baseline cytology-negative women and baseline FAM19A4/miR124-2 methylation-negative women were observed, with risk differences of –0.42% (95% CI –2.1 to 1.4) and –0.07% (95% CI –1.9 to 1.9), respectively. The 14-year cumulative cervical cancer incidence was significantly lower for methylation-negative women compared to cytology-negative women (risk difference 0.98%, 95% CI 0.26 to 2.0). Discussion: FAM19A4/miR124-2 methylation analysis has a good triage performance on baseline screening samples, with a cross-sectional CIN3+ sensitivity and long-term triage-negative CIN3+ risk equalling cytology triage. Therefore, FAM19A4/miR124-2 methylation analysis appears to be a good and objective alternative to cytology in triage scenarios in HPV-based cervical screening.